Orientacja marketingowa lubuskich przedsiębiorstw handlu detalicznego żywnością - Nowosadko, Krzysztof (Marketing Orientation of Food Retailing Enterprises in Lubuski Region, 2005)
A marketing oriented retailing firm is one that allows the wants and needs of customers to drive all the firm's strategic decisions. In order to create customer value, the company usually needs to conduct marketing research and use coherent combination of retailing variables called retailing-mix. Marketing research done among food stores in Lubuski region shows us, that most companies do not apply marketing orientation. Although most managers are conscious of nessesity to use marketing orientation, they conduct marketing research very rarely and use only selected and incoherent parts of retailing-mix.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 132-137